Teaching and Learning: Fostering Student Engagement, Critical Thinking, and Lifelong Learning Skills - Vaishali S. Vaghela; Dr. Falguni Parsana (Educational Administration: Theory and Practice, 2024)
This research paper aims to provide an in-depth analysis of the current state of education and learning practices, exploring various methodologies and technologies that promote effective learning outcomes. The report synthesizes and critiques existing literature on education, pedagogy, and cognitive science, highlighting the role of technology and innovative approaches in shaping the future of education. It also addresses challenges educators and learners face, proposes potential solutions, and identifies areas for future research and development. Through this comprehensive review, the paper seeks to contribute to advancing education and learning practices.